Uji Aktivitas Antioksidan Ekstrak Metanol dan Fraksi Kulit Buah Markisa Konyal (Passiflora Ligularis Juss) dengan Metoda DPPH: Penelitian - Meli Oktavia; Kharisma Jayak Pratama; Niken Luthfiyanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Antioxidants are compounds that can absorb or neutralize free radicals so that they can ward pff disease. Free radicals are foreign compounds that enter the body and damage the body’s immune system. Konyal passion fruit seeds (Passiflora ligularis Juss) have been widely used as passion fruit juice. Konyal passion fruit skin is a waste that can be used as a natural medicine. This study aims to determine the antioxidant activity of methanol extract and passion fruit skin fraction (Passiflora ligularis Juss) with the DPPH method using UV-VIS spectrophotometry at a maximum absorption wavelength of 517 nm with vitamin C as a comparator. The antioxidant activity test obtained IC50 Vitamin C : 3,054 µg/mL, IC50 methanol extract : 222,5 µg/mL, IC50 n-hexane fraction : 93,71 µg/mL, IC50 ethyl acetate fraction : 205,29 µg/mL and IC50 water fraction 124,76 µg/mL. Based on the IC50 value, it can be concluded that the antioxidant activity of the methanol extract is in the weak category, the n-heksan fraction is in te strong category, the ethyl acetate fraction is in the weak category and the water fraction is in the medium category.